Rosas - The Movie Anne Teresa De Keersmaeker's Counter Phrases - Mackrell, Judith (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Anne Teresa De Keersmaeker's Counter Phrases. PALABRAS CLAVE: Anne Teresa De Keersmaeker, Counter Phrases, Rosas Dance Company, Ictus Music Ensemble.